Literacy Movement in Indonesian and Spanish Context: A Comparative Case Study - Siti Hanna Sumedi (English Didactic, 2022)
Literacy movement serves a vital role to support, facilitate, and enhance literacy skills that is crucial to every human being overall development including character, social, and professional development. This comparative study on literacy movement in Indonesia and Spain analyze how these nations  promote literacy movement to accelerate students’ literacy skills and how the literacy movement implemented. Likewise, this study adopts a case study in which the data were derieved from observation protocol, document analysis, questionnaies, and interview transcripts. The data analysis revealed that Indonesia through Gerakan Literasi Nasional (GLN) promotes the literacy by creating literacy culture in educational ecosystem start in family, school, and society as a mean of long-life learning to improve life quality whereas the Ministry of Education Culture and Sport in Spain created a program called Act on The Improvement of the Quality of Education (LOMCE in Spanish) to promote and create a literate environment and improve educational result. As it further investigated, the most noticeable comparison between the practice of literacy movement in Indonesia and Spain is on the equality of literacy movement in every region. In Spain, the literacy movement is equally well-established in every region whereas the equality of literacy movement in Indonesia region is still not equal yet. In this matter, the implementation of literacy movement should be supported by qualified educators, appropriate materials, adequate infrastructure, and effective literacy policies in order to effectively promote the students’ literacy skills and development.